2018
DOI: 10.4194/1303-2712-v18_9_10
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The genetic integrity of the commercially important fish species is being compromised mainly due to artificial propagation. The present study evaluated the extent of genetic variability and assessed the population structure of Silver Carp (Hypophthalmicthys molitrix) in hatchery stocks of Punjab province, Pakistan using 16 species-specific microsatellite loci. The results revealed low-to-moderate scale of genetic variability in the hatchery stocks. The level of average observed heterozygosity varied from 0.377… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Compared nding to ours are also reported by Ahmed and Abbas (2018), Nazish et al (2018) and Diyei et al (2021).Analysis of molecular variance (AMOVA) was performed to determine genetic variability within and among populations, which speci ed that majority of variations (87.050%) were attributed to "within individuals" in wild populations. These results are in agreement withNazish et al (2018) in populations of Hypophthalmichthys molitrix inferred by microsatellite markers.Based on Nei's genetic distance, phylogenetic tree was constructed which yielded two clusters; PDK, RB, MD and JB populations were in one cluster while THW population alone was in second cluster. Although populations in one cluster are geographically separate, but share genetic similarity to similar origin.…”
supporting
confidence: 91%
“…Compared nding to ours are also reported by Ahmed and Abbas (2018), Nazish et al (2018) and Diyei et al (2021).Analysis of molecular variance (AMOVA) was performed to determine genetic variability within and among populations, which speci ed that majority of variations (87.050%) were attributed to "within individuals" in wild populations. These results are in agreement withNazish et al (2018) in populations of Hypophthalmichthys molitrix inferred by microsatellite markers.Based on Nei's genetic distance, phylogenetic tree was constructed which yielded two clusters; PDK, RB, MD and JB populations were in one cluster while THW population alone was in second cluster. Although populations in one cluster are geographically separate, but share genetic similarity to similar origin.…”
supporting
confidence: 91%
“…The maximum value of F IS was of the QBD, followed by FSD, BHL, LHR and FQB stocks respectively. Various studies on Cyprinids confirmed inbreeding depression in hatcheries (Sultana et al, 2015;Nazish et al, 2018;Ahmed and Abbas, 2018). The influence of geographical isolation with no exchange of brooders in relatively small populations might results into genetic diversity loss which in turn enhances the rate of inbreeding depression leading to increased risk of population's extinction (Hayer et al, 2014).…”
Section: Genetic Diversitymentioning
confidence: 93%
“…The reasons behind limited allelic diversity are the founders and bottleneck effect because managers in hatcheries have limited stock of brooders with poor genetic management (Wang et al, 2008). Loss of allelic diversity has also been reported by Alam and Islam (2005); Ahmed and Abbas (2018) in hatchery stocks of C. catla and Nazish et al (2018) in hatchery populations of Silver Carp. The lower values of Ho in this study might result of inbreeding depression and negative selection in the process of hatchery propagation plans (Zhou et al, 2011).…”
Section: Genetic Diversitymentioning
confidence: 97%